Math, asked by danishanwer, 1 year ago

Prove that 2(sin6A+cos6A)-3(sin4A+cos4A)+1=0​

Answers

Answered by parvathi008
0

Answer:

Step-by-step explanation:

Here take 6 as the common factor for (sin6A+cos6A) and

4 as the common factor for the other

Then we get ,

12(sinA+cosA)-12(sinA+cosA)

Which is equal to ZERO

HOPE TIS IS HELPFULL

PLS MARK ME AS THE BRAINLIEST

Answered by gangward688
0

Answer:

SIN6 A + COS 6A IS IN FORM OF A3 + B3

SIN6A+ COS 6 A = ( SIN 2 A + COS 2A ) 3 - 3 SIN2A * COS2A ( SIN 2A + COS 2A )

=> 13 - 3 SIN2A * COS2A

ALSO SIN4A + COS 4A IS IN FORM OF A2 + B2

SIN4A + COS 4A = ( SIN 2A + COS 2A)2 - 2 ( SIN 2A * COS 2A)

=> 1 2 - 2 ( SIN 2A * COS 2A)

Now, LHS = 2(sin6A + cos6A) - 3(sin4 + cos4) +1 =

2 (13 - 3 SIN2A * COS2A ) - 3 ( 1 2 - 2 SIN 2A * COS 2A) + 1

= 2 - 6 SIN 2A * COS 2A - 3 + 6 SIN 2A * COS 2A + 1

= 0

Step-by-step explanation:

Similar questions